FAKTOR-FAKTOR YANG MEMPENGARUHI PREFERENSI DEVELOPER DALAM MEMILIH LOKASI PERUMAHAN TERENCANA DI PESISIR KOTA BANDA ACEH - erhasy, amiratul jannah; Swasto, Deva Fosterharoldas (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2026)
One type of housing built in coastal areas is planned housing, where 54% of the total planned housing in Banda Aceh City is in coastal areas. This finding indicates a developer preference to build in the area. This study aims to explore developer preferences in determining the location of planned housing in coastal areas of Banda Aceh City. The approach used in this research is descriptive qualitative. The results showed that there were seven field findings that became factors of developer preferences in choosing planned housing locations, namely aspects of location, regulations and development permits, property markets, market preferences (consumers), cooperation and partnership systems, physical aspects and infrastructure and disaster risk mitigation. Factors that are very influential or most often appear in interviews are aspects of location, market potential and market preferences (consumers) related to economic aspects. The development of cities that lead to coastal areas opens up opportunities for developers to build housing in the area.